Removal of metals from industrial wastewater and urban runoff by mineral and bio-based sorbents. (1st March 2018) - Gogoi, Harshita; Leiviskä, Tiina; Heiderscheidt, Elisangela; Postila, Heini; Tanskanen, Juha
Abstract: The study was performed to evaluate chemically modified biosorbents, hydrochloric acid treated peat (HCl-P) and citric acid treated sawdust (Citric acid-SD) for their metal removal capacity from dilute industrial wastewater and urban runoff and compare their efficiency with that of commercially available mineral sorbents (AQM PalPower M10 and AQM PalPower T5M5 magnetite). Batch and column experiments were conducted using real water samples to assess the sorbents' metal sorption capacity. AQM PalPower M10 (consisting mainly of magnesium, iron and silicon oxides) exhibited excellent Zn removal from both industrial wastewater and spiked runoff water samples even at low dosages (0.1 g/L and 0.05 g/L, respectively). The high degree of Zn removal was associated with the release of hydroxyl ions from the sorbent and subsequent precipitation of zinc hydroxide. The biosorbents removed Ni and Cr better than AQM PalPower M10 from industrial wastewater and performed well in removing Cr and Cu from spiked runoff water, although at higher dosages (0.3–0.75 g/L). The main mechanism of sorption by biosorbents was ion exchange. The sorbents required a short contact time to reach equilibrium (15–30 min) in both tested water samples. AQM PalPower T5M5 magnetite was the worst performing sorbent, leaching Zn into both industrial and runoff water and Ni into runoff water. Column tests revealed that both HCl-P and AQM PalPower M10 were able to remove metals, although some leaching was witnessed, especially As from AQM PalPower M10. The low hydraulic conductivity observed for HCl-P may restrict the possibilities of using such small particle size peat material in a filter-type passive system. Graphical abstract: Image 1 Highlights: PalPower M10 removed zinc from dilute wastewaters most efficiently. Biosorbents were better for nickel and chromium removal from industrial wastewater. T5M5 was the poorest performing since it leached metal ions. The sorbents were more efficient in the treatment of spiked runoff waters. Sorbent type, treatment conditions and wastewater concentration are crucial factors.